High-temperature-resistant titanium-based composite material and casting preparation method thereof
Through the dual smelting process combined with vacuum consumable smelting and water-cooled copper crucible induction smelting, the problem of titanium-based composite castings prone to defects under high temperature conditions in the prior art is solved, and the preparation of titanium-based composite castings with high cleanliness, high quality and high performance is achieved, meeting the high-temperature service requirements in the aerospace field.
Patent Information
- Application Number
- CN202510023538.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
AI Technical Summary
It is difficult for the prior art to stabilize the preparation of high-clean, high-quality, and high-performance titanium-based composite castings in batches, especially under high temperature conditions, which are prone to defects such as pores, inclusions, shrinkage holes, etc., which affect the mechanical properties of the castings.
The dual smelting process is adopted, combining vacuum consumable smelting and water-cooled copper crucible induction smelting, and high-temperature resistant titanium-based composite castings are prepared through the dual smelting process. The vacuum consumable smelting is used to suppress component segregation, and the water-cooled copper crucible induction smelting improves the composition uniformity and mechanical properties of the castings.
The preparation of titanium-based composite castings with high cleanliness, high quality and high performance has been achieved, which significantly reduces the content of impurities, avoids defects such as shrinkage holes, and improves the tensile strength and yield strength of the castings at 700°C, meeting the high-temperature service requirements in the aerospace field.
Smart Images

Figure CN119800152A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium-based composite materials and methods for preparing castings thereof, and in particular relates to a method for preparing high-temperature resistant titanium-based composite material castings by a double smelting process. Background Art
[0002] In recent years, the demand for large and complex thin-walled parts in high-end fields such as aerospace has been increasing. As a near-net-shape forming technology, investment casting is suitable for mass production, which can greatly reduce or even avoid mechanical processing and significantly reduce production costs. Therefore, it shows greater superiority. However, it faces many problems when applied to the preparation of high-temperature resistant titanium-based composite components. For example, the highly active molten titanium-based alloy can react with almost all refractory materials at the interface, resulting in defects such as pores and inclusions, which seriously deteriorates the performance of the castings. At the same time, the molten titanium-based alloy has high viscosity and poor fluidity, and it is difficult to maintain the superheat at an ideal level during the filling process. The filling capacity is obviously insufficient, which greatly increases the difficulty of casting manufacturing. In addition, due to the large solidification shrinkage rate of titanium-based alloys, the solidification process is also prone to shrinkage, shrinkage, and cold cracking. Among them, shrinkage, shrinkage, as one of the most common casting defects in the alloy solidification process, will significantly deteriorate the mechanical properties of the casting, such as strength, fatigue life, creep ability, etc. In particular, the presence of reinforcing phases in titanium-based composites will significantly increase the viscosity of the molten metal and reduce the fluidity of the molten metal, which will greatly limit the solidification and shrinkage, and defects such as shrinkage and shrinkage are more likely to form. The addition of the reinforcement phase will also induce more complex metal liquid flow behavior, such as the Magnus phenomenon at the front of the metal liquid, further increasing the difficulty of casting. It is worth noting that parts used in aerospace and other fields (such as skeletons, engine blades, grilles, etc.) usually have complex thin-walled features, and the difficulty of filling special parts such as thin sections and sharp edges is greatly increased, and the tendency to crack is significantly increased; at the same time, the asymmetry of the structure puts higher requirements on the investment casting technology of titanium-based composite materials.
[0003] Therefore, the prior art still lacks a method for stably preparing high-cleanliness, high-quality, and high-performance titanium-based composite material castings in batches. Summary of the invention
[0004] In order to solve the problems of the prior art, the present invention proposes a high-temperature resistant titanium-based composite material and a method for preparing a casting thereof. The obtained high-temperature resistant titanium-based composite material can withstand a high temperature of 700°C, and a high-cleanliness, high-quality, and high-performance product can be obtained through a double smelting process.
[0005] The technical solution of the present invention is as follows:
[0006] A high temperature resistant titanium-based composite material comprises an alloy matrix and a reinforcement phase, wherein the alloy matrix comprises, by mass percentage, 4.5-7% Al, 2.5-5.5% Sn, 5-10% Zr, 0.5-3% Nb, 0.5-3% Mo, 0.3-2% W, 0.1-0.5% Si and the remainder Ti, and the reinforcement phase comprises, by volume percentage of the high temperature resistant titanium-based composite material, 0.1-2.5% TiC and 0.1-2.5% TiB.
[0007] According to some preferred embodiments of the present invention, the alloy matrix comprises, by mass percentage, the following: Al: 6%, Sn: 4%, Zr: 7%, Nb: 1%, Mo: 1%, W: 1%, Si: 0.2% and the balance Ti; the reinforcing phase comprises, by volume percentage of the high temperature resistant titanium-based composite material, TiC: 1.25% and TiB: 1.25%.
[0008] The present invention further provides a method for preparing a casting of the high temperature resistant titanium-based composite material, which comprises:
[0009] (1) drying raw materials of a high temperature resistant titanium-based composite material, wherein the raw materials include sponge titanium, high purity aluminum beans, Ti-Sn alloy, sponge zirconium, Al-Nb alloy, Al-Mo alloy, Al-W alloy, Si powder, B4C powder and C powder; mixing the dried raw materials except the dried B4C powder and C powder to obtain a mixture;
[0010] (2) evenly placing the dried B4C powder and C powder in the mixed material layer by layer to obtain a combined raw material, pressing the combined raw material into a cylindrical electrode rod, and welding a plurality of the electrode rods into a long electrode;
[0011] (3) subjecting the long electrode to vacuum consumable melting to obtain an ingot;
[0012] (4) dividing the ingot to obtain billets;
[0013] (5) induction melting the blank, keeping it warm after it melts, and then pouring it into the preheated ceramic shell through a centrifugal pouring process to obtain a casting;
[0014] (6) The casting is subjected to hot isostatic pressing treatment, and then cooled to room temperature to obtain the high temperature resistant titanium-based composite material casting.
[0015] According to some preferred embodiments of the present invention, the preparation method further comprises: mechanically treating the weld area of the long electrode obtained by welding so that there is no oxide layer and pollutants in the weld area.
[0016] According to some preferred embodiments of the present invention, the preparation method further comprises: removing an oxide layer and / or contaminants on the surface of the ingot, and then performing the segmentation.
[0017] According to some preferred embodiments of the present invention, the vacuum consumable melting uses a vacuum consumable melting furnace.
[0018] According to some preferred embodiments of the present invention, the induction melting uses a water-cooled copper crucible induction melting furnace.
[0019] According to some preferred embodiments of the present invention, the vacuum degree of the vacuum consumable smelting is less than 10 -2 Pa.
[0020] According to some preferred embodiments of the present invention, the voltage of the induction melting is 400-550 kV, the current is 1.5-2.5 A, and the vacuum degree is less than 10 -1 Pa.
[0021] According to some preferred embodiments of the present invention, the insulation time is 1 to 5 minutes.
[0022] According to some preferred embodiments of the present invention, the pouring temperature of the centrifugal pouring process is 1620-1800°C, the preheating temperature of the ceramic shell is 300-800°C, the pouring rate is 2-10kg / s, and the centrifugal speed is 150-450r / min.
[0023] According to some preferred embodiments of the present invention, the temperature of the hot isostatic pressing treatment is 950-1150° C., the heating rate is 10-15° C. / min, the pressure is 110-150 MPa, and the heat preservation and pressure holding time is 1.5-3.5 h.
[0024] According to some preferred embodiments of the present invention, the temperature for drying the raw material is 120-150° C. and the drying time is 12-48 hours.
[0025] According to some preferred embodiments of the present invention, obtaining the ceramic shell includes:
[0026] A. Obtain a metal mold with a cavity located in the middle of the mold and two exhaust channels on both sides of the cavity;
[0027] B. preparing a wax mold with a smooth surface by using a wax injection process to fill the wax material at a medium temperature;
[0028] C. Immersing the wax mold in the surface layer slurry for coating so that the surface is completely and evenly coated with the surface layer slurry, and then drying it under constant temperature and humidity conditions for 24 to 36 hours to obtain a surface layer shell; Immersing the surface layer shell in the back layer slurry for coating so that the surface is completely and evenly coated with the back layer slurry, and then drying it under constant temperature and humidity conditions for 24 to 36 hours to obtain an integral shell, the thickness of the integral shell is 7 to 20 mm; Dewaxing the integral shell, and then calcining it to obtain the target ceramic shell.
[0029] According to some preferred embodiments of the present invention, the surface layer slurry includes a surface layer ceramic material and a surface layer adhesive, the surface layer ceramic material includes Y2O3 and ZrO2, and the surface layer adhesive includes zirconium sol and ammonium zirconium carbonate sol; the back layer slurry includes a back layer ceramic material and a back layer adhesive, the back layer ceramic material includes mullite, and the back layer adhesive includes silica sol.
[0030] According to some preferred embodiments of the present invention, the constant temperature and humidity conditions are a temperature of 25° C. and a humidity of 45-60%.
[0031] According to some preferred embodiments of the present invention, the wax injection process uses a wax injection pressure of 30 to 50 kg / cm 2 , the temperature of the wax injection nozzle is 40-65℃, the temperature of the wax injection tube is 50-65℃, the temperature of the wax storage tank is 65-90℃, the insulation time of the wax storage tank is greater than 36h, the pressure is increased 1-3 times during the wax injection process, and the pressure is increased 1-3 times during the wax replenishment process.
[0032] According to some preferred embodiments of the present invention, the dewaxing pressure of the dewaxing treatment is 0.5-1.0 MPa, and the dewaxing time is 5-15 min.
[0033] According to some preferred embodiments of the present invention, the calcination temperature is 750-1250° C. and the calcination time is 1-5 hours.
[0034] According to some preferred embodiments of the present invention, the Sn content in the Ti-Sn alloy is 80wt.%, the Nb content in the Al-Nb alloy is 83wt.%, the Mo content in the Al-Mo alloy is 52wt.%, and the W content in the Al-W alloy is 53wt.%.
[0035] The present invention has the following beneficial effects:
[0036] (1) The present invention provides a method for preparing high-temperature resistant (700°C and above) titanium-based composite material castings by a dual process of vacuum consumable melting and water-cooled copper crucible induction melting, which fully combines the technical advantages of vacuum consumable melting and water-cooled copper crucible induction melting, can effectively inhibit component segregation, promote the homogenization of casting composition, reduce the content of impurity elements such as N, H, and O, and make the mechanical properties of the casting at a high level;
[0037] (2) The preparation method of the present invention can significantly improve the product qualification rate, and provides a new idea for the stable batch preparation of high-cleanliness, high-quality, and high-performance titanium-based composite material castings;
[0038] (3) The preparation method of the present invention can be carried out on the basis of existing conventional production equipment, without adding new production equipment or production lines, and can be quickly promoted and applied;
[0039] (4) The titanium-based composite material casting prepared by the present invention has a tensile strength of 632 MPa at 700°C, a yield strength of 586 MPa, and an elongation of 14.2%, which can better meet the 700°C service requirements in the aerospace field. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 700°C tensile properties of the casting in Example 2. DETAILED DESCRIPTION
[0041] The present invention is described in detail below in conjunction with the embodiments and drawings, but it should be understood that the embodiments and drawings are only used to exemplify the present invention and do not constitute any limitation on the protection scope of the present invention. All reasonable changes and combinations within the scope of the inventive concept of the present invention fall within the protection scope of the present invention.
[0042] Example 1
[0043] The 700°C resistant titanium-based composite castings were prepared by the following steps:
[0044] (1) drying raw materials of a 700° C. resistant titanium-based composite material at 130° C. for 36 h, the raw materials comprising sponge titanium, high-purity aluminum beans, TiSn alloy, sponge zirconium, Al-Nb alloy, Al-Mo alloy, Al-W alloy, industrial Si powder, B4C powder and C powder, wherein the Sn content in the Ti-Sn alloy is 80 wt.%, the Nb content in the Al-Nb alloy is 83 wt.%, the Mo content in the Al-Mo alloy is 52 wt.%, and the W content in the Al-W alloy is 53 wt.%; mixing the dried raw materials except the dried B4C powder and C powder to obtain a mixture;
[0045] (2) evenly placing the dried B4C powder and C powder in a mixed material layer by layer to obtain a combined raw material, pressing the combined raw material into a cylindrical electrode rod, welding a plurality of electrode rods into a long electrode, and mechanically treating the weld area to ensure that there is no oxide layer and contaminants in the weld area;
[0046] (3) Place the welded long electrode in a vacuum consumable melting furnace and melt it repeatedly for 3 times. Each time the melting needs to be turned over, the vacuum degree in the furnace is always less than 10 -2 Pa, and a 100 kg ingot was obtained;
[0047] (4) subjecting the obtained ingot to mechanical processing to remove the surface oxide layer and other surface contaminants, and then dividing it into billets suitable for induction melting in a water-cooled copper crucible;
[0048] (5) Prepare the metal mold and ceramic shell required for casting;
[0049] (6) Placing the ceramic shell in a water-cooled copper crucible induction melting furnace, and at the same time, placing the blank in a water-cooled copper crucible for melting, the melting voltage is 480-500 kV, the current is 1.5-2.5 A, and the vacuum degree in the furnace is always less than 10 -1 Pa, after the blank is completely melted, keep warm for 3 minutes, and then use centrifugal pouring process to pour the casting under vacuum conditions: pouring temperature is 1650℃, shell preheating temperature is 350℃, pouring rate is 2kg / s, and centrifugal speed is 150r / min;
[0050] (7) The casting obtained after pouring was subjected to hot isostatic pressing treatment, with the hot isostatic pressing temperature being 1050°C, the heating rate being 15°C / min, the pressure being 120 MPa, and the holding time being 2 h. The casting was then furnace cooled to room temperature to obtain a titanium-based composite material casting.
[0051] The preparation of the metal mold and the ceramic shell includes:
[0052] A. Prepare a metal mold, wherein the cavity is located in the middle of the mold and two exhaust channels are provided on both sides of the cavity;
[0053] B. preparing a wax model, including: placing a medium temperature filling wax material in a wax injection machine to prepare a wax model with good surface finish and no defects, wherein the wax injection pressure is 35-40 kg / cm 2 , the wax injection nozzle temperature is 55-60℃, the wax injection tube temperature is 60-65℃, the wax storage tank temperature is 75-90℃, and the wax storage tank insulation time is greater than 36h; in order to improve the quality of the wax model, the wax injection process is pressurized twice and the wax replenishment process is pressurized twice;
[0054] C. Preparing a ceramic shell, comprising: immersing the obtained wax mold into a surface layer slurry, applying 3 layers so that the surface of the wax mold is completely and evenly coated with the surface layer slurry, and then drying it for 24 hours under constant temperature and humidity conditions of 25° C. and 45-60% humidity to obtain a surface layer shell; immersing the surface layer shell into a back layer slurry, applying 7 layers so that the surface of the wax mold is completely and evenly coated with the back layer slurry, and then drying it for 24 hours under constant temperature and humidity conditions to obtain an integral shell with a thickness of 12 mm; placing the obtained integral shell in a dewaxing kettle for steam dewaxing treatment The dewaxing pressure is 0.8MPa and the dewaxing time is 10min. The shell after dewaxing is placed in a muffle furnace for calcination at a temperature of 1000°C and a calcination time of 2.5h to obtain the target ceramic shell. The surface layer slurry includes a surface layer material and a surface layer binder. The surface layer material is Y2O3-stabilized ZrO2 powder / sand, and the surface layer binder is zirconium sol and ammonium zirconium carbonate sol. The back layer slurry includes a back layer material and a back layer binder. The back layer material is mullite powder / sand, and the back layer binder is silica sol.
[0055] The 700°C resistant titanium-based composite material obtained in this embodiment includes an alloy matrix and a reinforcement phase, wherein the specific components of the alloy matrix include (mass percentage, wt.%): Al: 6%, Sn: 4%, Zr: 7%, Nb: 1%, Mo: 1%, W: 1%, Si: 0.2% and the remainder Ti; the reinforcement phase includes (volume percentage, vol.%): TiC: 1.25%, TiB: 1.25%.
[0056] The impurity elements of the titanium-based composite castings were tested, and the results were as follows: N: 0.008wt.%, H: 0.001wt.%, O: 0.07wt.%. The castings were tested by X-ray nondestructive testing, and no internal defects such as shrinkage and shrinkage cavities were found. The castings were tested for tensile properties at 700°C, and their tensile strength, yield strength, and elongation were 652MPa, 590MPa, and 13.8%, respectively.
[0057] Example 2
[0058] The 700°C resistant titanium-based composite castings were prepared by the following steps:
[0059] (1) Drying the raw materials of a 700° C. resistant titanium-based composite material at 130° C. for 36 h, wherein the raw materials include sponge titanium, high-purity aluminum beans, Ti-Sn alloy, sponge zirconium, Al-Nb alloy, Al-Mo alloy, Al-W alloy, industrial Si powder, B4C powder and C powder, wherein the Sn content in the Ti-Sn alloy is 80 wt.%, the Nb content in the Al-Nb alloy is 83 wt.%, the Mo content in the Al-Mo alloy is 52 wt.%, and the W content in the Al-W alloy is 53 wt.%; mixing the dried raw materials except the dried B4C powder and C powder to obtain a mixture;
[0060] (2) evenly placing the dried B4C powder and C powder in a mixed material layer by layer to obtain a combined raw material, pressing the combined raw material into a cylindrical electrode rod, welding a plurality of electrode rods into a long electrode, and mechanically treating the weld area to ensure that there is no oxide layer and contaminants in the weld area;
[0061] (3) Place the welded long electrode in a vacuum consumable melting furnace and melt it repeatedly for 3 times. Each time the melting needs to be turned over, the vacuum degree in the furnace is always less than 10 -2 Pa, and a 100 kg ingot was obtained;
[0062] (4) subjecting the obtained ingot to mechanical processing to remove the surface oxide layer and other surface contaminants, and then dividing it into billets suitable for induction melting in a water-cooled copper crucible;
[0063] (5) Prepare the metal mold and ceramic shell required for casting;
[0064] (6) Placing the ceramic shell in a water-cooled copper crucible induction melting furnace, and at the same time, placing the blank in a water-cooled copper crucible for melting, the melting voltage is 480-500 kV, the current is 1.5-2.5 A, and the vacuum degree in the furnace is always less than 10 -1 Pa, after the blank is completely melted, keep warm for 3 minutes, and then use centrifugal pouring process to pour the casting under vacuum conditions, the pouring temperature is 1750℃, the shell preheating temperature is 700℃, the pouring rate is 3kg / s, and the centrifugal speed is 450r / min;
[0065] (7) The casting obtained after pouring was subjected to hot isostatic pressing treatment, with the hot isostatic pressing temperature being 1020°C, the heating rate being 15°C / min, the pressure being 130 MPa, and the holding time being 2 h. The casting was then furnace cooled to room temperature to obtain a titanium-based composite material casting.
[0066] The preparation of the metal mold and the ceramic shell includes:
[0067] A. Prepare a metal mold, wherein the cavity is located in the middle of the mold and two exhaust channels are provided on both sides of the cavity;
[0068] B. preparing a wax model, including: placing a medium temperature filling wax material in a wax injection machine to prepare a wax model with good surface finish and no defects, wherein the wax injection pressure is 35-40 kg / cm 2 , the wax injection nozzle temperature is 55-60℃, the wax injection tube temperature is 60-65℃, the wax storage tank temperature is 75-90℃, and the wax storage tank insulation time is greater than 36h; in order to improve the quality of the wax model, the wax injection process is pressurized twice and the wax replenishment process is pressurized twice;
[0069] C. Preparing a ceramic shell, comprising: immersing the obtained wax mold into a surface layer slurry, applying 4 layers so that the surface of the wax mold is completely and evenly coated with the surface layer slurry, and then drying for 36 hours under constant temperature and humidity conditions of 25° C. and 45-60% humidity to obtain a surface layer shell; immersing the surface layer shell into a back layer slurry, applying 9 layers so that the surface of the wax mold is completely and evenly coated with the back layer slurry, and then drying for 36 hours under constant temperature and humidity conditions to obtain an integral shell with a thickness of 15 mm; placing the obtained integral shell in a dewaxing kettle for steam dewaxing The dewaxing pressure is 0.8MPa and the dewaxing time is 15min. The shell after dewaxing is placed in a muffle furnace for baking treatment. The baking temperature is 1000℃ and the baking time is 3h to obtain a ceramic shell. The surface layer slurry includes a surface layer material and a surface layer binder. The surface layer material is Y2O3-stabilized ZrO2 powder / sand, and the surface layer binder is zirconium sol and ammonium zirconium carbonate sol. The back layer slurry includes a back layer material and a back layer binder. The back layer material is mullite powder / sand, and the back layer binder is silica sol.
[0070] The 700°C resistant titanium-based composite material obtained in this embodiment includes an alloy matrix and a reinforcement phase, wherein the specific components of the alloy matrix include (mass percentage, wt.%): Al: 6%, Sn: 4%, Zr: 7%, Nb: 1%, Mo: 1%, W: 1%, Si: 0.2% and the remainder Ti; the reinforcement phase includes (volume percentage, vol.%): TiC: 1.25%, TiB: 1.25%.
[0071] The impurity elements of the titanium-based composite casting were tested, and the results were as follows: N: 0.007wt.%, H: 0.001wt.%, O: 0.075wt.%. The casting was tested by X-ray nondestructive testing, and no internal defects such as shrinkage and shrinkage holes were found. The casting was tested for tensile properties at 700℃, and its tensile strength, yield strength and elongation were 632MPa, 586MPa and 14.2% respectively. Figure 1 shown.
[0072] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A high temperature resistant titanium-based composite material, characterized in that: The invention comprises an alloy matrix and a reinforcement phase, wherein the alloy matrix comprises, by mass percentage, 4.5-7% Al, 2.5-5.5% Sn, 5-10% Zr, 0.5-3% Nb, 0.5-3% Mo, 0.3-2% W, 0.1-0.5% Si and the balance Ti, and the reinforcement phase comprises, by volume percentage of the high-temperature resistant titanium-based composite material, 0.1-2.5% TiC and 0.1-2.5% TiB.
2. The high temperature resistant titanium-based composite material according to claim 1, characterized in that: The alloy matrix comprises, by mass percentage, 6% Al, 4% Sn, 7% Zr, 1% Nb, 1% Mo, 1% W, 0.2% Si and the balance Ti; the reinforcing phase comprises, by volume percentage of the high-temperature resistant titanium-based composite material, 1.25% TiC and 1.25% TiB.
3. The method for preparing a casting of a high temperature resistant titanium-based composite material according to claim 1 or 2, characterized in that: It includes: (1) drying raw materials of high temperature resistant titanium-based composite materials, wherein the raw materials include sponge titanium, high purity aluminum beans, Ti-Sn alloy, sponge zirconium, Al-Nb alloy, Al-Mo alloy, Al-W alloy, Si powder, B4C powder and C powder; mixing the dried raw materials except the dried B4C powder and C powder to obtain a mixture; (2) evenly placing the dried B4C powder and C powder in the mixed material layer by layer to obtain a combined raw material, pressing the combined raw material into a cylindrical electrode rod, and welding a plurality of the electrode rods into a long electrode; (3) subjecting the long electrode to vacuum consumable melting to obtain an ingot; (4) dividing the ingot to obtain billets; (5) induction melting the blank, keeping it warm after it melts, and then pouring it into a preheated ceramic shell through a centrifugal pouring process to obtain a casting; (6) The casting is subjected to hot isostatic pressing treatment, and then cooled to room temperature to obtain the high temperature resistant titanium-based composite material casting.
4. The preparation method according to claim 3, characterized in that: It also includes: mechanically treating the weld area of the long electrode obtained by welding to make the weld area free of oxide layer and pollutants; and / or removing the oxide layer and pollutants on the surface of the ingot, and then performing the segmentation.
5. The preparation method according to claim 3, characterized in that: in, The vacuum consumable melting uses a vacuum consumable melting furnace; and / or the induction melting uses a water-cooled copper crucible induction melting furnace.
6. The preparation method according to claim 3, characterized in that: in, The vacuum degree of the vacuum consumable melting is less than 10 -2 Pa; and / or, the voltage of the induction melting is 400-550 kV, the current is 1.5-2.5 A, and the vacuum degree is less than 10 - 1 Pa; and / or, the holding time is 1 to 5 min; and / or, the pouring temperature of the centrifugal pouring process is 1620 to 1800 ° C, the preheating temperature of the ceramic shell is 300 to 800 ° C, the pouring rate is 2 to 10 kg / s, and the centrifugal speed is 150 to 450 r / min; and / or, the temperature of the hot isostatic pressing treatment is 950 to 1150 ° C, the heating rate is 10 to 15 ° C / min, the pressure is 110 to 150 MPa, and the holding time is 1.5 to 3.5 h; and / or, the temperature of the raw material drying treatment is 120 to 150 ° C, and the drying time is 12 to 48 h.
7. The preparation method according to claim 3, characterized in that: The ceramic shell is obtained by: A. Obtain a metal mold with a cavity located in the middle of the mold and two exhaust channels on both sides of the cavity; B. preparing a wax mold with a smooth surface by using a wax injection process to fill the wax material at a medium temperature; C. Immersing the wax mold in the surface layer slurry for coating so that the surface is completely and evenly coated with the surface layer slurry, and then drying it under constant temperature and humidity conditions for 24 to 36 hours to obtain a surface layer shell; Immersing the surface layer shell in the back layer slurry for coating so that the surface is completely and evenly coated with the back layer slurry, and then drying it under constant temperature and humidity conditions for 24 to 36 hours to obtain an integral shell, the thickness of the integral shell is 7 to 20 mm; Dewaxing the integral shell, and then calcining it to obtain the target ceramic shell.
8. The preparation method according to claim 7, characterized in that: in, The surface layer slurry includes a surface layer ceramic material and a surface layer adhesive, the surface layer ceramic material includes Y2O3 and ZrO2, and the surface layer adhesive includes zirconium sol and ammonium zirconium carbonate sol; the back layer slurry includes a back layer ceramic material and a back layer adhesive, the back layer ceramic material includes mullite, and the back layer adhesive includes silica sol.
9. The preparation method according to claim 7, characterized in that: in, The constant temperature and humidity conditions are 25°C and 45-60% humidity; and / or the wax injection pressure used in the wax injection process is 30-50 kg / cm 2 , the wax injection nozzle temperature is 40-65°C, the wax injection tube temperature is 50-65°C, the wax storage tank temperature is 65-90°C, the wax storage tank insulation time is greater than 36h, the wax injection process is pressurized 1-3 times, and the wax replenishment process is pressurized 1-3 times; and / or, the dewaxing pressure of the dewaxing treatment is 0.5-1.0MPa, and the dewaxing time is 5-15min; and / or, the roasting temperature is 750-1250°C, and the roasting time is 1-5h.